2000
DOI: 10.1128/jvi.74.8.3598-3604.2000
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Virion Host Shutoff (vhs) Activity Alters Periocular Disease in Mice

Abstract: During lytic infection, the virion host shutoff (vhs) protein of herpes simplex virus (HSV) mediates the rapid degradation of RNA and shutoff of host protein synthesis. In mice, HSV type 1 (HSV-1) mutants lacking vhs activity are profoundly attenuated. HSV-2 has significantly higher vhs activity than HSV-1, eliciting a faster and more complete shutoff. To examine further the role of vhs activity in pathogenesis, we generated an intertypic recombinant virus (KOSV2) in which the vhs open reading frame of HSV-1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 45 publications
1
50
1
Order By: Relevance
“…Such a role for T cells in clearance from dermal lesions has been reported (32)(33)(34)51). It follows then that mice in which a stronger or more competent immune response has been induced would be able to more effectively prevent development of blepharitis (41). It is interesting that a corresponding decrease in virus shed into tear film was not observed in our experiments, although the titers of virus in the periocular skin were not determined.…”
Section: ϫ 10contrasting
confidence: 42%
“…Such a role for T cells in clearance from dermal lesions has been reported (32)(33)(34)51). It follows then that mice in which a stronger or more competent immune response has been induced would be able to more effectively prevent development of blepharitis (41). It is interesting that a corresponding decrease in virus shed into tear film was not observed in our experiments, although the titers of virus in the periocular skin were not determined.…”
Section: ϫ 10contrasting
confidence: 42%
“…However, a caveat to this observation was that there was a 10-fold reduction in the HSV-2 challenge employed to infect mice compared to the HSV-1 challenge applied to the eye. In another study, an intertypic recombinant HSV-1 strain expressing the HSV-2 (strain 333) virion host shutoff (vhs) protein was found to elicit less blepharitis associated with increased clearance of the recombinant virus in comparison to the parental or marker-rescued virus following ocular infection (31). Since the HSV-2-encoded vhs protein displayed significantly greater activity than its HSV-1 counterpart in vitro, those authors concluded that vhs expression alters the host immune response to the pathogen, including the activation of T cells and the IFN pathway (31).…”
mentioning
confidence: 99%
“…Alternatively, the attenuation of HSV-1 and HSV-2 vhs null mutants within 24 to 48 h postinfection (47)(48)(49)(50) suggests a pivotal role for mediators of innate immunity in controlling acute infection. A key mediator of innate antiviral immunity to virus infection is the alpha/beta interferon (IFN-␣/␤) response.…”
mentioning
confidence: 99%
“…In vivo, vhs null mutants of HSV-1 and HSV-2 are profoundly attenuated, implicating vhs as a virulence factor that helps HSV establish robust infection. HSV-1 lacking vhs activity replicates to 1,000-fold-lower titers in the cornea, trigeminal ganglia, and brain of mice than wildtype virus and has impaired capacity to enter the central nervous system, establish latency, and undergo reactivation (48)(49)(50). vhs-deficient HSV-2 strains (333-vhsB or 333d41) also replicate much less efficiently than wild-type virus in the genital mucosa and nervous tissue of mice and cause less disease (47).…”
mentioning
confidence: 99%